THE EFFECTIVENESS OF USING SILENT WAY METHOD ON STUDENTS’ VOCABU-LARY ACHIEVEMENT (QUASI-EXPERIMENTAL RESEARCH AT THE SECOND GRADE OF SMPN 29 BENGKULU TENGAH) - Meji Lestari, Lesi; Riswanto; Martina, Feny (Yayasan Darussalam Bengkulu, 2022)
This study's main goal was to ascertain whether the silent way method had a signiﬁcant effect on the vocabulary achievement of eighth-grade students at SMPN 29 Bengkulu Tengah. In this research, a quasi-experimental design was used. In this study, there were two classes of students. The first group includes the experimental class, while the second includes the control class. The two groups were then given a pre-test and a post-test. With the two classes, various strategies were employed. The experimental class was instructed using the silent way method, whereas the control class was instructed using the direct method, as a result of the application of this strategy in classroom instruction. This study's sampling technique was a purposive sampling method. During the gathering of data, the researcher used the test as a research tool. The test consists of 20 valid multiple-choice questions that are presented in this method. The researcher tested the validity of the hypothesis using the independent sample t-test in the SPSS 22 program. According to the findings of the hypothesis test, the independent sample t-test (sig. 2-tailed) result was 0.000, which is less than 0.05, and the t-count value is 4.698, which is more than the t-table df=22 (2.07387). Therefore, it can be stated that the silent way method of teaching had a significant effect on vocabulary achievement among students at SMPN 29 Bengkulu Tengah.